Jarbalo, Leavenworth County - Harrell, Mallory (Kansas State University, The Chapman Center for Rural Studies, 2016)
This is a study of Jarbalo in Alexandria Township, Leavenworth County. While never officially incorporated, it is a community with a curious history that survives even now. This exhibit uses field work, photographs, interviews, written histories, and newspapers
Mallory Harrell, “Jarbalo, Leavenworth County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/170.
Keywords: Leavenworth County; Tonganoxie; Delaware Indian Reserve; Doc and William Mason; Jarbalo Rural High School; Opliger Grocery